Profile of Dental Caries in Eastern and Western Parakanã Children at Amazônia Paraense, Brazil - Marlene Ribeiro de Oliveira; Angélica Maria Cupertino Lopes Marinho; Cristiane Baccin Bendo; Aluísio Ferreira Celestino Junior; Simone Dutra Lucas; Saul Martins Paiva (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the prevalence of dental caries in children from 18 months to 5 years of age in eastern (near urban centers) and western (far from urban centers) Parakanã, verify the influence of proximity to non-indigenous cultures, and compare with other ethnicities and non-indigenous. Material and Methods: The universe of children was examined by one researcher in a cross-sectional study. Descriptive analysis and the Mann-Whitney test (p<0.05) were performed. Results: It was observed that 68.8% (N = 53) of children from 18 to 36 months of age presented dmft = 0 (without caries), while 12.5% (N = 6) of children of five years of age presented this condition. For children between 18 and 36 months, the average dmft values were 0.74 (SD=1.91) for eastern children and 1.25 (SD=1.65) for western children. At five years of age, the average dmft values were 4.35 (SD=3.29) and 3.75 (SD=2.05) for eastern and western, respectively. Mann-Whitney test (p<0.05) showed no difference between East and Western children. When compared with non-indigenous Brazilian children, the values behaved similarly. Conclusion: Knowledge of the epidemiological profile of dental caries in Indigenous Parakanã children is relevant both in planning oral health actions for this population and for aggregating information, which is still scarce for Indigenous.